KH Abdurrahman Wahid's Study: Revitalization of the Meaning of Just and Civilized Humanity - Amma Chorida Adila; Ahmad Taufiq; Nurul Hikmah Sofyan (Alfuad: Jurnal Sosial Keagamaan, 2023)
Abstract:  Human case studies are interesting to analyze from a variety of different perspectives. Regarding humanitarian cases in Indonesia, in 2022 there have been phenomenal human rights violations. Gus Dur's version of humanism is religious humanism adhering to the principles of Islamic teachings, but its actualization does not only touch the religious field. This study used a qualitative method with a literature review approach. The goal is to learn about KH Abdurrahman Wahid's thoughts on applying humanism theory to humanitarian issues.The research results obtained indicate that the basic foundation of the Indonesian nation is Pancasila, which consists of five precepts with fundamental values. Of course, in understanding these values, there is a meaning contained therein. This research tries to connect the humanitarian cases that occurred in Indonesia with the theory of humanism. The theory of humans serves as a foundation for KH Abdurrahman Wahid's ideas He is an intellectual figure and scholar whose knowledge comes from all over the country. Human cases are caused by the morality of each individual and socio-cultural, economic, political, and religious changes. In this case, Gus Dur actualizes human values that are just and adaptable to the concept of humanizing humans. In order to create world peace, a sense of involvement with the suffering of fellow human beings must be strengthened, not bypunishing those who suffer.